The Lesbian and the Room: Proust’s Invention of Difference - christina l stevenson (Studies in 20th & 21st Century Literature, 2015)
More than a conflict between external activity and internal sanctuary, the room in Proust's writing is a figure that weaves a complex fabric of narrative perception. If, in his youth, Proust's narrator believed the room to be a refuge for containing an eroticized feminine Other, the wiser narrative voice reveals the room as offering the disruption rather than the fulfillment of desire. The perspective of childhood is interwoven with the retrospective voice of the adult narrator who dispels the naïve fantasies of the desiring youth. This paper illustrates that confronting the failure of desire becomes imperative for the Proustian narrator in his journey toward authorship. The retrospective failure in/of the room in Sur la lecture is repeated in A la recherche du temps perdu. In the latter text, the room merges with its female occupant and captive, Albertine, whose suspected lesbian desire occasions the narrator’s loss of illusions. This failure of the narrator’s desire appears as a purposeful event authorially enacted in order to both demonstrate and provoke the narrator’s writerly talents. Lesbian desire gets written into the story of Albertine in order to produce the possibility of the young protagonist’s fall from innocence into the role of the seasoned, cynical author. In order for Marcel to become a writer, he must create the conditions of his own authorship, in this case the twin images of the degraded room and the lesbian lover, two fantasies of sacred femininity come undone.
Keywords: Proust; queer reading; psychoanalysis; space; Days of Reading; Sur la lecture; In Search of Lost Time; A la recherche du temps perdu